2019
DOI: 10.1186/s12936-019-2954-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent preventive treatment of malaria delivered to primary schoolchildren provided effective individual protection in Jinja, Uganda: secondary outcomes of a cluster-randomized trial (START-IPT)

Abstract: Background Intermittent preventive treatment (IPT) of malaria is recommended as policy for certain high-risk populations, but not currently for schoolchildren. A cluster-randomized trial was conducted to evaluate the effect of IPT with dihydroartemisinin–piperaquine (DP) on primary schoolchildren in Jinja, Uganda. Results of the impact of IPT of schoolchildren on community-level transmission have been reported previously. Here, secondary outcomes from a school-based survey are presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…School-aged children are significant reservoirs of human-to-mosquito transmission. 16 , 17 Three studies, 27 , 28 , 37 reported that intervention significantly decreased the prevalence of gametocytes, the parasite life-stage required for transmission. Staedke and colleagues 36 found that treating school-aged children decreased infection in the surrounding community by a small but statistically significant proportion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School-aged children are significant reservoirs of human-to-mosquito transmission. 16 , 17 Three studies, 27 , 28 , 37 reported that intervention significantly decreased the prevalence of gametocytes, the parasite life-stage required for transmission. Staedke and colleagues 36 found that treating school-aged children decreased infection in the surrounding community by a small but statistically significant proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Because malaria immunity increases with cumulative exposure to P falciparum parasites, we stratified results by age to explore the effect of intervention among children aged 5 years to less than 10 years versus children aged 10 years or older to less than 15 years. Because two of the larger trials 35 37 fundamentally differed from others, we also did sensitivity analyses excluding these datasets. We used Stata/IC 15 software for all analyses.…”
Section: Methodsmentioning
confidence: 99%
“… 48 We therefore power our study to detect differences of this magnitude (0.2 log 10 ) or (in some cases) smaller. Among 5 to 15 year olds in this study setting, previous studies have reported malaria prevalence of >50% based on microscopy; 21 22 we assume malaria prevalence of > 60% based on PCR.…”
Section: Methods and Analysismentioning
confidence: 98%
“…20 In a recently concluded trial in Uganda, IPT in schoolchildren was shown to be beneficial in protecting individual children and reducing community transmission of malaria. 21 22 …”
Section: Introductionmentioning
confidence: 99%
“…Other preventive interventions have been trialed or piloted, including intermittent preventive treatment in school children (IPTsc), mass drug administration (MDA) and post-discharge malaria chemoprevention (PMC) [13,14]. PMC being one of the most recently investigated interventions, we sought to better understand how it could be implemented.…”
Section: Introductionmentioning
confidence: 99%